Cisplatin resistance in nonsmall cell lung cancer: Role of platinum accumulation and cell membranes. - Popovic, Predrag. (University of Ottawa (Canada), 1994)
A cisplatin resistant cell line named E-8/0.7 was derived from the nonsmall cell lung cancer HTB 56 cell line. According to IC$\sb{50}$ estimations, E-8/0.7 cells were approximately 7.7 times more resistant to cisplatin than were HTB 56 cells. Uptake of cisplatin 100 $\mu$M over 1 hour was measured by atomic absorption spectrophotometry, and showed around a 30% lower uptake in E-8/0.7 cells compared to HTB 56 cells. Barotropic behaviour was analyzed by pressure tuning infrared spectroscopy. In the CH symmetric stretching region, we found a lower break point (and consequently lower membrane fluidity) in E-8/0.7 cells compared to the parent cell line. Lipid analyses of the two cell lines showed a higher cholesterol to phospholipid molar ratio in E-8/0.7 than in HTB 56 cells. Moreover, concentration of sphingomyelin was higher in E-8/0.7 cells than in HTB 56 cells.
Keywords: Biology, Cell.